Splitting and reorientation of π-conjugation by an unprecedented photo-rearrangement reaction. Issue 3 (4th December 2019) - Inaba, Yuya; Yoneda, Tomoki; Kitagawa, Yuichi; Miyata, Kiyoshi; Hasegawa, Yasuchika; Inokuma, Yasuhide
Abstract : π-Conjugation of a dodecahexaene was regioselectively cleaved by an unprecedented photo-rearrangement into an orthogonally oriented bis(hexatriene) in which two chromophores are arranged in a close proximity to exhibit excitonic interactions. Abstract : A dodecahexaene analogue cross-conjugated with four carbonyl groups was prepared from an aliphatic tetraketone. Exposure to LED light (>420 nm) led to the splitting of the dodecahexaene conjugation into two hexatriene subunits, connected through a stereogenic carbon atom. The two triene subunits exhibited excitonic coupling in the UV-Vis absorption and CD spectra.